Signs of chronic thromboembolic pulmonary hypertension in acute pulmonary embolism: results from the FOCUS study. (3rd October 2022) - Mavromanoli, A C; Valerio, L; Bunck, A C; Kreitner, K F; Ley, S; Gertz, R J; Rosenkranz, S; Konstantinides, S V; Barco, S
Abstract: Background/Introduction: Chronic thromboembolic pulmonary hypertension (CTEPH) is considered to be a late complication of acute pulmonary embolism (PE). However, up to one third of CTEPH patients do not report prior symptomatic venous thromboembolism (VTE). Furthermore, a substantial proportion of patients presenting with an acute PE event may exhibit radiological signs of chronicity at baseline computed tomography pulmonary angiography (CTPA). Purpose: To determine the prevalence of baseline radiological parameters indicating chronic thrombosis or pulmonary hypertension, and ultimately pre-existing CTEPH, among patients with acute PE enrolled in the prospective multicentre Follow-Up after Acute Pulmonary Embolism (FOCUS) cohort study. Methods: Patients with acute symptomatic PE and absence of a known history of CTEPH, enrolled at two large FOCUS centres, were included. The assessment of index CTPA scans was conducted by two independent expert radiologists who were unaware of the clinical characteristics and the follow-up data of the patients. CTPA parameters indicating chronicity were prespecified on the basis of recently proposed criteria in the literature. A third independent expert radiologist provided an assessment in case of disagreement between the first two. Baseline radiological data were prospectively validated with the aid of two-year prospective clinical follow-up data focusing on CTEPH and the post-PE syndrome (co-primary outcomes of the FOCUS study). Results: A total of 303 patients (median age: 63 years, 44.6% women) were included. In >95% of the patients, the expert radiologists could confirm signs of acute PE at baseline CTPA. Radiological signs of chronic thrombi or pulmonary hypertension at baseline were detected in 46 (15.2%) patients. In 8 patients, the expert radiologists agreed on the presence of pre-existing CTEPH based on their interpretation of the overall radiological pattern. During follow-up, five (1.7%; 95% CI 0.7–3.8%) of 303 patients were diagnosed with CTEPH, over a median time of 95 days after baseline. Four of them were among the 8 patients in whom the radiological experts suspected pre-existing CTEPH at baseline, and among the 46 patients in whom CTPA findings suggesting chronic thrombi or chronic pulmonary hypertension were present at baseline. The use of the predefined individual parameters of chronicity from the literature also helped identifying patients with chronic disease, and could be used as a tool for screening acute PE patients for pre-existing CTEPH. Conclusion: A substantial proportion of patients who are diagnosed with CTEPH during follow-up after acute PE may already have pre-existing CTEPH at the time of the index event. An intensified follow-up programme and focussed screening for CTEPH should be considered in patients with signs of chronicity at baseline CTPA. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Bayer Health Care